Avaliação da genotoxicidade de resinas acrílicas de uso odontológico por meio do teste de micronúcleo em células esfoliadas da mucosa bucal - Cruz, João Pedro Pedrosa (2019)
Acrylic resins are widely used in dentistry as both restorative and auxiliary materials. However, little is known about their genotoxicity. Thus, the aim of this work was to evaluate the genotoxic potential of acrylic resins used in dentistry with the Micronucleus Test in exfoliated buccal mucosal cells. In addition to the occurrence of micronuclei, degenerative nuclear alterations indicative of apoptosis (pycnose, karyorrhexis, and condensed chromatin) and necrosis (karyolysis, additionally) were investigated in cells of two distinct groups of individuals: 1) occupationally exposed professionals; 2) children and adolescents using orthodontic appliances made with acrylic resins. For evaluation in the group of exposed professionals, exfoliated cheek cells from 60 individuals of both sexes were equally divided into 3 groups: professionals exposed to acrylic resins, professionals non-exposed to acrylic resins and non-dental professionals. For evaluation in the group of children and adolescents, exfoliated cells from the cheek and palate mucosa of 30 individuals of both sexes in the age group of 6-12 years were evaluated. Collections were performed before the installation of appliances and after a period of 15 to 21 days. Cytological analyses were blindly performed under optical microscopy according to protocols suggested by Tolbert; Shy; Allen (1991, 1992) and Thomas et al. (2009). A minimum of 2,000 cells per region collected for each individual was considered for analysis. Regarding occupational exposure, no difference was observed between groups regarding the occurrence of micronuclei (p> 0.05) and karyolysis (p> 0.05). The isolated evaluation of alterations indicative of apoptosis revealed that karyorrhexis, condensed chromatin and pycnose were significantly more frequent among exposed professionals when compared to non-dental professionals, but no differences were observed when compared to non-exposed professionals. These, however, differed from non-dental professionals only for the occurrence of karyorrhexis. The combined evaluation of these changes revealed differences between groups of exposed and non-exposed professionals compared to non-dental professionals. Regarding the evaluation of children and adolescents using orthodontic appliances, no difference was observed between the two moments regarding the occurrence of micronuclei and degenerative nuclear alterations indicative of apoptosis and necrosis in cheek cells (p> 0.05). The evaluation of palate cells revealed a significant increase in the occurrence of micronuclei and nuclear alterations indicative of apoptosis (p <0.01), but not of karyolysis (p> 0.05). It could be concluded that professionals are exposed to agents capable of causing genotoxicity expressed by the increase in nuclear alteration rates indicative of apoptosis. Occupational exposure to acrylic resin monomers could a priori contribute to increased apoptosis, but the results obtained here do not allow such a conclusion, since non-exposed professionals did not differ from exposed ones. In addition, direct contact with orthodontic appliances induces an increase in the occurrence of chromosomal damage and degenerative nuclear alterations. It is important to consider that in addition to methylmethacrylate, the main monomer of acrylic resins, it is possible that local trauma caused by the devices may have stimulated the cell renewal process, interfering with differences observed. The results obtained encourage the conduction of further studies to evaluate the real genotoxic potential of acrylic resins